GoldAid : An Integrated Safety System Leveraging IoT and Advanced Algorithms for Rapid Medical Aid in the Gold en Hour - Tripathi, Anushka; Sahni, Arpit; Somanchi, Srikar; Mantha, Sresthavadhani; Hammad Khan, Mohammed; Srivastava, Abhishek (IEEE sensors journal, 2024)
98.44% accuracy, and the system achieves a latency of